Academic Senate Minutes 2008-05-22 - Academic Senate:::::::::
Chair Report. Agenda amended and approved. Minutes of 5/8/08 approved. Revision to Political Science program – approved. Approval of Terry Lease and Sam Brannen for At-Large Senators to Executive Committee '08 – '09. Chair-Elect Report. Update on WASC. Academic Freedom Policy amended and approved. Constitution and by-laws amendments for CFA and SAEM membership approved for vote of all faculty. Diversity Resolution amended and approved. Revision to the Faculty Consultation in University Decision Making policy approved. Changing of the Guard.